X^2-5x-48=0

Simple and best practice solution for X^2-5x-48=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X^2-5x-48=0 equation:


Simplifying
X2 + -5x + -48 = 0

Reorder the terms:
-48 + X2 + -5x = 0

Solving
-48 + X2 + -5x = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + X2 + 48 + -5x = 0 + 48

Reorder the terms:
-48 + 48 + X2 + -5x = 0 + 48

Combine like terms: -48 + 48 = 0
0 + X2 + -5x = 0 + 48
X2 + -5x = 0 + 48

Combine like terms: 0 + 48 = 48
X2 + -5x = 48

Add '5x' to each side of the equation.
X2 + -5x + 5x = 48 + 5x

Combine like terms: -5x + 5x = 0
X2 + 0 = 48 + 5x
X2 = 48 + 5x

Simplifying
X2 = 48 + 5x

Reorder the terms:
-48 + X2 + -5x = 48 + 5x + -48 + -5x

Reorder the terms:
-48 + X2 + -5x = 48 + -48 + 5x + -5x

Combine like terms: 48 + -48 = 0
-48 + X2 + -5x = 0 + 5x + -5x
-48 + X2 + -5x = 5x + -5x

Combine like terms: 5x + -5x = 0
-48 + X2 + -5x = 0

The solution to this equation could not be determined.

You can always share this solution

See similar equations:

| X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 |

Equations solver categories